Zero-fluoroscopy versus fluoroscopy-guided catheter ablation in ventricular arrhythmia: A systematic review and meta-analysis - Irnizarifka, Irnizarifka; Tristan, Christopher D.; Wijayanto, Matthew A.; Myrtha, Risalina; Modesty, Kyra; Rahma, Annisa A.; Budiono, Enrico A.; Rahman, Awalil R. K.; Hamka, Muhammad Farid; Ilyas, Muhana F. (Narra J, 2025)
Catheter ablation has been the go-to treatment for ventricular arrhythmia, with traditional fluoroscopy-guided and non-zero fluoroscopy (NZF) catheter ablation posing high radiation risk for operators and patients. Zero-fluoroscopy technique offers elimination of radiation risk; however, its efficacy and safety in ventricular arrhythmia patients are not well explored. The aim of this study was to systematically evaluate the effectiveness, safety, and feasibility of zero-fluoroscopy ablation on ventricular arrhythmia patients. This study only included relevant studies comparing zero-fluoroscopy and NZF in ventricular arrhythmia ablation that were identified from Scopus, PubMed, and ScienceDirect (up to June 20, 2024). The quality of the study was assessed using the ROBINS-I tool, and the meta-analysis was conducted using a random-effect model. Out of 383 studies found, nine cohort studies were included with 1.408 patients. There was no significant difference in the acute procedural success rate of the zero-fluoroscopy and NZF (relative risk: 1.01; 95%CI: 0.95–1.07; p=0.69), with a similar recurrence rate (p=0.88; for four studies; n=374), and comparable procedural time (mean difference: -19.22 minutes; 95%CI: -41.16–2.72; p=0.09). Adverse events such as pericardial effusion, pseudoaneurysm, and hematoma were similar between zero-fluoroscopy and NZF. Overall, zero-fluoroscopy catheter ablation has demonstrated non-inferiority as a treatment option for ventricular arrhythmia ablation. As zero-fluoroscopy eliminates radiation risk without compromising procedural efficacy, zero-fluoroscopy has the potential to become a widely adopted approach for catheter ablation in ventricular arrhythmia.